MOTIVASI KERJA GURU DALAM PEMBELAJARAN DI SEKOLAH MENENGAH ATAS NEGERI 1 BANUHAMPU - NURVIRA GUSWANTI (Universitas Negeri Padang, 2016)
Objective of this study is to see how the work motivation of teachers. The population is 50 employees were taken by proportional sampling population. This is a research instrument with Likert scale questions modelsthat been tested for validity and reliability. Data were analyzed by using the average value and the level of performance. The results of this research work is motivated teacher in SMA I Banuhampu be in either category.